Hepatitis B and C Viruses’ Infection and Associated Factors among Pregnant Women Attending Antenatal Care in Hospitals in the Amhara National Regional State, Ethiopia - Mulat Dagnew; Yihenew Million; Mucheye Gizachew; Setegn Eshetie; Gashaw Yitayew; Lakachew Asrade; Mulat Adefris; Feleke Moges; Moges Tiruneh (International Journal of Microbiology)
Introduction. Hepatitis virus infection is a major public health burden and silent killer disease in sub-Saharan Africa, including Ethiopia. Therefore, this study aimed to investigate the prevalence of hepatitis B and C viruses and associated factors among pregnant women attending an antenatal clinic in three tertiary hospitals in Amhara National Regional State, Ethiopia. Methods. A cross-sectional study was conducted among 1121 pregnant women. Data on sociodemographic and associated factors were collected using a structured questionnaire. Serum samples were tested for hepatitis B surface antigen (HBsAg) and anti-hepatitis C virus antibody (anti-HCV) using ELISA. SPSS version 20 was used for data analysis, and a multivariable logistic regression analysis was used to assess the relationship between factors associated with hepatitis B virus and hepatitis virus C infection. Results. A total of 1121 pregnant women were included in the study. The mean age of study participants was 27.2 ± 4.8 yrs. The majority of pregnant women (895 (79.8%)) were from urban areas. The overall seroprevalence of HBsAg and anti-HCV antibody was 52 (4.6%) and 18 (1.6%), respectively. The coinfection rate of HBV/HCV was 1.4% (1/69). Ten (19.2%) of HBV positive cases were coinfected with HIV. There were no coinfections of HCV and HIV. Interestingly, pregnant women with a history of multiple sexual partners (AOR = 3.2, 95% CI, 1.7–7.6), blood transfusion (AOR = 7.6, 95% CI, 2.9–16.9), family history of HBV (AOR = 3.5, 95% CI, 1.7–7.6), being HIV-positive (AOR = 2.5, 95% CI, 1–5.9), and tattooing (AOR = 2, 95% CI, 1–3.8) were significant predictors of HBV infection. Similarly, young age (17–25 yrs) (AOR = 3.2, 95% CI, 1.8–8.6) and no educational background (AOR = 5, 95 CI, 1.7–14.8) were significant predictors of HCV infection. Conclusions. Hepatitis B and C viruses’ infection was intermediate among pregnant women; some risk factors were significantly associated with the majority of cases. Infants born from these infected mothers are at risk of infection. This calls for screening and integration of HBV prevention of mother-to-child transmission (PMTCT) into HIV. Thus, the provision of health education on hepatitis B and C viruses’ transmission, vaccination, and screening of all pregnant women routinely are essential for the prevention of these viruses.